East Timor, Birth of a Nation. Episode One: Rosa's Journey - Acquisto, Luigi (Film Australia ; Abracadabra Films, 2002)
Verzio FF Submission Duration: 00:52:00 “East Timor, Birth of a Nation” is the story of a country rising from the ashes of a violent past. The people of the world's youngest nation are now rebuilding their lives, reconciling past injustice and staking a claim on the future. This is the story of Rosa Martins, a 26 years old widow and mother of six children. Her father was killed and her mother starved to death while fleeing from invading Indonesian forces in 1975. Now, with the Indonesians gone Rosa travels to the distant towns of Venilale and Los Palos where three of her children live in orphanages.